Synthesis and activation of carbon nanospheres for adsorption of organic pollutants - Tan, Yu Xin. (2009)
Activated carbon is widely used in waste water treatment given its impressive adsorptive properties, and glucose synthesized carbon has proven to be an environmental friendly as well as a toxic free alternative relative to the conventional carbon sources. Hence this study aims to determine the most effective form of activation for carbons nanospheres (CNS) synthesized from glucose and to derive a method for recycling and reactivating the spent CNS after its application. Methylene blue (MB) was used as a model organic pollutant to test the adsorption ability of the activated carbon. Results showed that NaOH is the most effective activating agent among the various reagents tested. This may be explained by the cationic nature of MB molecule and the enhancement in stability of the OH functional groups that coat the surface of glucose synthesized CNS. Further testing on the optimum dosage of NaOH revealed that 0.02M NaOH is the most favorable concentration to activate 0.05gram of CNS in 100ml of aqueous solution. Chemical regeneration, which involved 8 different solvents, and thermal regeneration of the spent activated CNS done in the scope of this study did not reap fruitful results. This suggests that MB may have chemisorbed instead of adsorbed onto the surface. To further support this study, a comparison test with tyre activated carbon in terms of their BET surface area, MB adsorption efficiency, and maximum loading of MB molecules onto each samples’ surface were done to assess how glucose synthesized CNS fair with another common form of activated carbon.